Assessing and addressing diabetes distress among adults with type 2 diabetes: An online survey of Australian general practitioners. Issue 5 (October 2022) - McMorrow, Rita; Hunter, Barbara; Hendrieckx, Christel; Speight, Jane; Emery, Jon; Manski-Nankervis, Jo-Anne
Abstract: Aim: Diabetes distress is experienced by up to 36% of adults with type 2 diabetes. Australian type 2 diabetes guidelines recommend annual assessment of diabetes distress in general practice. This study explores general practitioners' knowledge, current practice, and factors influencing implementation of guidelines, including Person Reported Outcome Measure (PROM) use. Methods: A cross-sectional online survey was disseminated via e-mail to 4776 Australian general practitioners listed on the Australasian Medical Publishing Company database. Results: 264 (5%) surveys were returned. 75% indicated that general practitioners were the most appropriate professionals to assess diabetes distress. Sixteen percent reported asking about diabetes distress during type 2 diabetes consultations more than half the time, with 13% using a PROM more than half the time: 64% use the Kessler-10, and 1.9% use the Problem Areas in Diabetes (PAID) scale. While general practitioners had positive beliefs about the consequences of assessing and addressing diabetes distress, they also reported barriers in motivation, environment, and knowledge of guidelines. Conclusion: Most respondents endorsed general practitioners' role in assessing diabetes distress, but few ask about or assess diabetes distress in routine consultations. To support uptake of guideline recommendations for diabetes-specific PROM use, environmental factors, specifically time, need to be addressed. Highlights: Surveyed GPs indicated they are the most appropriate healthcare professionals to assess diabetes distress. GPs held positive beliefs about the consequences and their capabilities when assessing diabetes distress. Few surveyed GPs used the Problem Area in Diabetes scale to assess diabetes distress. Time is the most frequently reported barrier to using Person Reported Outcome Measures. GPs prefer Person Reported Outcome Measures to be integrated with electronic medical records.